APLIKASI GAME MEDIA PEMBELAJARAN BAHASA INGGRIS PADA ANAK - ANAK SDN MELAYU 2 BANJARMASIN MENGGUNAKAN ADOBE FLASH CS6 - Said Muhammad; Rohayati Rohayati; Said Alwi Zulfikri Hairi (P3M Politeknik Negeri Banjarmasin, 2020)
This study is aimed to create an English learning media game application as an interesting alternative learning system in order to increase English knowledge and children's interest in learning. It is also to presents the English learning media game application quickly and precisely to the students of SDN Melayu 2 Banjarmasin. The research method used is Applied Research which also used primary data sources and secondary data. Data collection techniques used were interviews, observation, and literature. As for the system development method, the author used the Waterfall method by analyzing the system, functional and non-functional requirements and PIECES analysis by using the Adobe Flash CS6 application program to make English learning media for students. The results of this study are the formation of learning media game applications so that learning for users could make changes in mindset, have a learning spirit and increase the interest of students in learning and are more relevant. The installation could also be accessed easily just by using a computer device.